Strengthening Students’ Entrepreneurial Intentions through the Entrepreneurial Ecosystem: Supporting the Sustainable Development Goal on Quality Education - Nurlaila Nurlaila; Arina Salsabilla Haq (Journal of Psychology and Culture Behavior in SDGs, 2025)
Objective: This study aims to examine how key components of the entrepreneurial ecosystem, including access to funding, government programs and support, physical infrastructure, and entrepreneurship education, influence students’ entrepreneurial intentions. The research aligns with the Sustainable Development Goals (SDGs), particularly SDG 4.4, which focuses on enhancing skills for employment, decent work, and entrepreneurship among youth. Method: A quantitative approach was employed in this research. The subjects of this research are undergraduate students from the 2021 and 2022 cohorts of the Economics Education Study Program, Faculty of Economics and Business, State University of Surabaya, with a sample of 125 students selected through simple random sampling. Data were collected using a questionnaire and analyzed using Structural Equation Modeling (SEM) with the help of WarpPLS software. Results: The results demonstrate that all four ecosystem components have a significant and positive effect on entrepreneurial intention, with entrepreneurship education and training exerting the strongest influence. These findings validate the Theory of Planned Behavior (TPB) by linking ecosystem factors with key psychological determinants such as attitudes, subjective norms, and perceived behavioral control. Novelty: The novelty of this research lies in its contextual focus on pre-service economics teachers as future agents of entrepreneurial education and in its contribution to SDG oriented entrepreneurship policy and curriculum development in higher education.